Intracellular delivery of methylprednisolone by dendrimer-based nanoparticles improves locomotor outcomes after spinal cord injury - Cerqueira, Susana R. (2012)
Spinal cord injuries (SCI) still remain a major challenge in current biomedical research. In spite of several advances in the understanding of its mechanisms there has not been an equal significant translation into the clinics. As a result, there is no effective treatment that can overcome the biochemical and cellular adverse reactions that lead to a chronic severely impaired condition. One of the first opportunities to minimize these drastic consequences is to control the secondary events that follow the trauma. We are proposing the local delivery of an anti-inflammatory corticosteroid - methylprednisolone (MP) – in an attempt to modulate the noxious effects of the inflammation in the acute SCI. A sustained delivery as the one provided by these nanoparticles (NP) can be highly advantageous, maximizing the drug’s potency in the target site. Therefore, we synthesized MP-loaded NPs composed of an inner poly/(amido)amine (PAMAM) dendrimeric core and grafted with carboxymethylchitosan (CMCht). Chemical and biological characterization studies were carried out showing that the NPs are stable in acidic and neutral buffer solutions. Also, the viability of primary glial cultures was not compromised by the presence of 200 lg/mL of NP. In turn, an MP action in microglial cultures was observed in dosages above 1 mg/ mL showing that MP is being released from the NPs inside the cells. The uptake profile of these NPs is time dependent and reaches itsmaximum 24 h after incubation with astrocytes, oligodendrocytes and microglia. In a preview of a possible therapeutic effect, the NPs were administered in hemisected spinal cord injured rats. To assess the efficacy of local injections around the lesion site the animals were sacrificed 3 h after surgery and frozen sections were observed. The fluorescently labeled-NPs were detected in the injury and in the surrounding spinal tissue indicating a successful delivery of the NP to the spinal tissue. The local injections were repeated in hemisected rats that were kept for 1 month, performing the BBB locomotory test weekly. Significant differences in the BBB test were found between the MPloaded NPs injected rats and the sham group as well as the ones injected with MP, demonstrating a favorable action of the MP-NPs in the acute phase of the injury. This work revealed that sustained delivery of MP via a NP system can be highly beneficial in the management of the secondary injury that follows SCI improving the overall functional outcome of the injured animals.